2013
DOI: 10.1007/s00330-013-2833-y
|View full text |Cite
|
Sign up to set email alerts
|

Subtractionless first-pass single contrast medium dose peripheral MR angiography using two-point Dixon fat suppression

Abstract: • MRA is increasingly used for vascular applications. • Dixon imaging offers an alternative to image subtraction for fat suppression. • Subtractionless first-pass peripheral MRA is possible using two-point Dixon fat suppression. • Subtractionless peripheral MRA is possible at 1.5 T a single contrast medium dose. • Subtractionless first-pass peripheral MRA provides good image quality with few non-diagnostic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…Previous studies have shown promising results of two-point Dixon fat suppression MRA to increase image quality by suppressing the signal of fat adjacent to vessels [16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown promising results of two-point Dixon fat suppression MRA to increase image quality by suppressing the signal of fat adjacent to vessels [16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Aside from the array itself, imaging the pelvis without using breath holding typically introduces motion, another dimension of potential degradation of image quality. Such motion-related artifacts may be mitigated by other methods, such as subtractionless Dixon imaging [3740]. …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in cases that are expected to have rapid arterial-to-venous transit, a targeted time-resolved acquisition at the calf-foot station prior to or after the bolus chase runoff could be performed, as is done with hybrid MRA acquisitions. Third, motion-related artifacts can potentially be addressed using a two-point Dixon technique for subtractionless MRA (33). Another option is to use a blood pool contrast agent, which would enable a quick steady-state acquisition at the abdomen-pelvis station following the first-pass run if needed (34).…”
Section: Discussionmentioning
confidence: 99%